Busuu in Improving Student German Vocabulary - Chantika, Anggie; Hasmawati, Hasmawati; Azizah, Laelah (Phonologie : Journal of Language and Literature, 2024)
Abstract. This study aims to determine the planning, implementation, and results of German vocabulary improvement using Busuu application for class XI students of SMA Negeri 14 Makassar. This research is a classroom action research consisting of two cycles, each of which contains planning, implementation, observation and reflection. The research data consisted of two types, namely qualitative data which is a description of the results of implementation and observation during learning and quantitative data in the form of test results of students' vocabulary improvement through Busuu application. The average value of vocabulary improvement of XI IPS 3 students in cycle 1 was 65.60% (Fair) and increased in cycle II to 78.25% (Good). The results showed that the use of Busuu application can increase students' German vocabulary during learningKeyword: Learning media, vocabulary, Busuu app, German language